Do seasonal dietary shifts by Temminck's pangolins compensate for winter resource scarcity in a semi-arid environment?. (February 2022) - Panaino, Wendy; Parrini, Francesca; Phakoago, Makabudi V.; Smith, Dylan; van Dyk, Gus; Fuller, Andrea
Abstract: In response to food scarcity, animals may increase foraging time or shift their diet by including more profitable prey items. Aardvarks ( Orycteropus afer ) in the semi-arid Kalahari region of southern Africa died, apparently of starvation, because they did not shift their diet when their primary food resource declined following a drought. Whether other myrmecophagous (ant- and termite-eating) mammals alter their diet in response to food scarcity is unclear. We investigated the feeding behaviour (through faecal analysis and direct observations) of six free-living, myrmecophagous Temminck's pangolins ( Smutsia temminckii ), for two years in the Kalahari. We also collected data on climate and ant and termite availability. Winter was characterised by low prey abundance, but pangolins predominantly selected three insect genera, namely Crematogaster ants, Anoplolepis ants, and Trinervitermes termites, regardless of food availability . Pangolins responded to winter resource scarcity by increasing the proportion of consumed Trinervitermes termites, but the shift did not prevent low energy intake during that period. During the winter of the drier of the two years, pangolins increased foraging time and fed on energy-rich prey. Whether the relatively low dietary flexibility of pangolins will allow them to meet their energy demands as insect populations decline with climate change is not known. Highlights: We used faecal analysis to assess the diet of six pangolins in the Kalahari. Pangolins fed on Crematogaster and Anoplolepis ants, and Trinervitermes termites. The diet changed seasonally, but that did not prevent low energy intake in winter. Foraging for longer and on energy-rich prey occurred when resources were scarce.